Exploring Trends in Financial Performance Metrics: An In-Depth Study of Nepalese Banks Over the Past Decade - Subedi, Purushottam (NPRC Journal of Multidisciplinary Research, 2024)
This study investigates the trends in Return on Assets (ROA) and Return on Equity (ROE) within Nepalese banks over the past decade, while also assessing the growth of banking infrastructure, including branches, ATMs, and card usage. Utilizing a descriptive and correlational research design, secondary data spanning from fiscal years 2070/71 to 2079/80 was analyzed, drawing on monthly records from 20 commercial banks to yield 2,400 observations. Data was collected from annual reports, the Nepal Rastra Bank, the Central Bureau of Statistics, and economic surveys. Results revealed a significant initial rise in both ROA and ROE, indicating robust profitability, followed by notable declines that suggest underlying structural weaknesses in the banking sector. The expansion of banking infrastructure was substantial, with a marked increase in branches and ATMs between 2074 and 2075, positively correlating with financial performance indicators such as total deposits and loans. The study concludes that enhancing banking infrastructure is crucial for improving financial stability and performance in Nepal's banking sector. The findings highlight the interconnectedness of physical banking presence and financial health, emphasizing the need for strategic reforms. The novelty of this research lies in its comprehensive analysis of the relationships between banking metrics and financial outcomes in the Nepalese context, providing valuable insights for policymakers and financial institutions aiming to navigate current challenges and foster sustainable growth.